Parviphycus bompardii sp. nov. and P. albertanoae (Gelidiales, Rhodophyta), two species misidentified as Gelidiella ramellosa in the Mediterranean Sea - Bottalico, Antonella; Russo, Christian; Furnari, Giovanni; Perrone, Cesira (Phytotaxa, 2015)
A critical re-examination of both recent and historical herbarium specimens from the Mediterranean Sea attributed to Gelidiella ramellosa highlighted that previous identifications were incorrect. Our investigations have demonstrated that the examined specimens actually belong to the genus Parviphycus; some of them must be attributed to the recently described P. albertanoae and some to the undescribed species Parviphycus bompardii. The new species shows morphological features that distinguish it from the other congeners and represents the fifth species of the genus occurring in the Mediterranean Sea. Parviphycus bompardii is readily recognizable for both branching pattern and characteristics of tetrasporangial sori. Results of this study suggest a re-examination of previous Mediterranean records attributed to G. ramellosa and a much more accurate approach to future records of Gelidiales. An identification key to Mediterranean species of Parviphycus is also presented based on our results and also on a review of the literature.